ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PROPERTIES DAN REAL ESTATE DI BEI - Anessya Anggia Savitri; Rahman Amrullah Suwaidi (POLITEKNIK LP3I JAKARTA, 2024)
Industrial development during the transformation period as a policy of every business entity whose existence is urgent for the welfare of all audiences and economic growth, with the principle of building an independent and ever-growing economy. The observation is intended to analyze the impact of profitability, liquidity, solvency, and activity ratio variables on company value in the property and real estate sector listed on the IDX for the period 2020-2022. The observation has a population of 85 companies in the property and real estate sector listed on the IDX. The purposive sampling technique was used to take samples in the observation. The sample obtained from this technique was 64 companies. The analysis method for programming observation data is multiple linear regression processed with SPSS. The research indicates that starting from liquidity, solvency, and activity ratio there is a match with the company's value, while profitability is the opposite.